Analysis of Maintenance Management and Building Care In the State University of Padang - Kombino, Budi Agus; Hidayat, Benny; Ophiyandri, Taufika (Jurnal Rekayasa Sipil (JRS-Unand), 2019)
Since establishment on September 1, 1954, the State University of Padang (UNP) has undergone many changes, especially in the number and shape of existing buildings. It requires a Maintenance and Building Care management system. The purpose of this research is to identify the implementation of  PU Ministerial regulation number: 24/PRT/M/2008, about: Guidance of Maintenance and Building Care at UNP. The research method is a descriptive method. Data is collecting by direct observation, distributing questionnaires to 70 respondents divided according to their functions (16 leaders, 12 managers, 30 executors, and 12 students), and collecting maintenance documents and building drawings, literature from research results, journals, building maintenance, and care manuals. The questionnaire is filled in numerical form and processed using an Excel program using descriptive and quantitative analysis that is displayed in the form of bar charts. The results of data processing show that the level of application of Public Works Ministerial regulation at UNP is between 53.01%-74.5%, which is categorized as ‘good enough’ to ‘Good’. The results of this calculation cannot be used as a conclusion in the study, the data obtained need to be validated with other data, including data from direct observations in the field, as well as interviews with several leaders at UNP. After validation with the data, it can be concluded thoroughly that the implementation of the Public Works Ministerial regulation at UNP falls into the ‘less good’.